Operation and Professional Developement - Chaturani, Sagar (ATLAS SkillTech University, 2024)
During my time at Mahakaal Shipping Pvt Ltd, I had the privilege of engaging in diverse roles that allowed me to contribute significantly to the company's operations and growth. As part of the team, I actively participated in Social Media Coordination, Inventory Management, and Customer Support, gaining a holistic understanding of these critical business functions. My role extended beyond operational tasks. I demonstrated a strong command over website backend management, utilizing my skills to streamline order modifications and create insightful customer analytics. This technical proficiency not only enhanced operational efficiency but also contributed to data-driven decision- making. One of my major accomplishments during my tenure was my role as a Operation and professional development. In this capacity. This initiative involved strategic planning, Customer Relationship, and a deep understanding of marketing dynamics. By successfully establishing the company's presence on Trade India, I contributed to expanding its digital footprint and engaging with a broader audience. In summary, my experience at Mahakaal Shipping Pvt Ltd encapsulated multifaceted contributions, ranging from Team Coordination and Inventory Management to Customer Support and impactful Marketing endeavors. My proficiency in management further augmented these contributions. I am grateful for the opportunity to have been part of a dynamic team and to have played a pivotal role in the company's operational and Sales advancement.
Project Report on Operation and Professional Developement (2022-2024) Under the Guidance of Prof. Ameya Ambulkar
Keywords: Inventory Management; Customer Support; Marketing; Digital Marketing